STIMULASI KETERAMPILAN MOTORIK HALUS ANAK USIA 4-5 TAHUN MENGGUNAKAN PERMAINAN MENYAMBUNG JALAN DENGAN MEDIA SEDOTAN - Nahda Wafiah Idrus; Eka Sufartianinsih Jafar (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Children's fine motor skills are very important to pay attention to and develop from the golden age. Efforts that can be made to improve children's fine motor skills are to provide stimulation from the outside such as providing educational games that can help improve fine motor development. This service aims to stimulate fine motor skills of early childhood at UPT PPRSA Inang Matutu. Children's fine motor stimulation is provided through interesting and fun educational game methods. The game is named “The Road-Connecting Game”. Games are designed using simple and low-budget tools and materials so that they can be a reference for parents and social workers in stimulating children's fine motor development. The subjects in this study were APM class A at UPT PPRSA Inang Matutu as many as 10 people aged 4-5 years. Data collection techniques in this study used observation and interview methods. This development uses the class action method through 6 stages, namely initial reflection, field introduction, finding solutions, action planning, action implementation, observation, and evaluation. The results of this service show that there is an increase in children's fine motor skills after carrying out the game. It is hoped that the use of educational game tools can be carried out to stimulate aspects of development adapted to the stages of age and child development.